Enhancement of microalgal lipid production in municipal wastewater: Fixation of CO2 from the power plant tail gas. (December 2019) - Tu, Renjie; Jin, Wenbiao; Han, Song-fang; Zhou, Xu; Wang, Jiaqi; Wang, Qing; He, Zhongqi; Ding, Wanqing; Che, Lin; Feng, Xiaochi
Abstract: Insufficient carbon source is the main limiting factor for microalgae cultivation in wastewater. The use of power plant tail gas to provide carbon source for microalgae could simultaneously reduce CO2 and promote both microalgal growth and lipid production. In this work, the effect of CO2 from the power plant tail gas on Chlorella pyrenoidosa grown in wastewater was primarily studied. The results showed that the dry weight and lipid productivity of C. pyrenoidosa was significantly increased by 84.92 and 74.44% in the presence of power plant tail gas, respectively. Meanwhile, the optimum carbon fixation sequestration of microalgae was 1.121 g/L and the average carbon fixation rate was 0.209 g/(L·d), which was 134.22% and 107.07% higher than the blank group. The effects of various toxic components of power plant tail gas on the growth of microalgae were also investigated. The results showed that the pretreatment process including desulfurization and denitrification of the power plant tail gas is needed before the utilization of CO2 . Highlights: CO2 from the power plant tail gas enhanced the growth of C.pyrenoidosa in sewage. The optimum carbon fixation rate of C.pyrenoidosa was increased by 61.34%. Microalgal dry weight and lipid productivity were increased by 84.92 and 74.44%.